Marx and the alternative to capitalism - Allen, Kieran, 1954- (Pluto Press, 2011)
"Dispensing with the dryness of traditional explanations of Marx, Kieran Allen shows how Marx's ideas apply to modern society. The first section briefly outlines Marx's life and the development of his work, then goes on to clearly explain his key theories, including historical materialism and surplus value. The second section examines alternatives to capitalism, the concept of 'anti-capitalism' and provides concrete, contemporary examples of Marx's theories being put into practice in today's world. This book provides a crucial alternative introduction to Marx for undergraduates in sociology and politics"--Page 4 of cover